2005
DOI: 10.1007/s10096-005-0056-0
|View full text |Cite
|
Sign up to set email alerts
|

Spread of ampicillin/vancomycin-resistant Enterococcus faecium of the epidemic-virulent clonal complex-17 carrying the genes esp and hyl in German hospitals

Abstract: The incidence of vancomycin-resistant Enterococcus faecium isolation was low ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(108 citation statements)
references
References 64 publications
1
99
0
5
Order By: Relevance
“…Retrospective epidemiological analyses in hospitals experiencing larger VRE outbreaks revealed that changes in specific procedures such as antibiotic policy, staffing, infection prevention and control regimes were, in some instances, significantly associated with increasing VRE rates, whereas in other settings this could not be shown. Increased VRE prevalence is partly associated with spread of single, distinct epidemic clones or types (Klare et al, 2005;Top et al, 2007;Bonora et al, 2007;Werner et al, 2007c;Valdezate et al, 2009;Zhu et al, 2010;Johnson et al, 2010;Hsieh et al, 2010). In contrast, VRE outbreaks in single centres tend to be polyclonal suggesting a diverse population of hospital-acquired E. faecium strains and a highly mobile resistance determinant capable of spreading widely among suitable recipient strains (Yoo et al, 2006;Deplano et al, 2007;Kawalec et al, 2007;Borgmann et al, 2007;Werner et al, 2007c;Hsieh et al, 2009).…”
Section: Prevalence Of Vre Among the Hospital Settingmentioning
confidence: 99%
“…Retrospective epidemiological analyses in hospitals experiencing larger VRE outbreaks revealed that changes in specific procedures such as antibiotic policy, staffing, infection prevention and control regimes were, in some instances, significantly associated with increasing VRE rates, whereas in other settings this could not be shown. Increased VRE prevalence is partly associated with spread of single, distinct epidemic clones or types (Klare et al, 2005;Top et al, 2007;Bonora et al, 2007;Werner et al, 2007c;Valdezate et al, 2009;Zhu et al, 2010;Johnson et al, 2010;Hsieh et al, 2010). In contrast, VRE outbreaks in single centres tend to be polyclonal suggesting a diverse population of hospital-acquired E. faecium strains and a highly mobile resistance determinant capable of spreading widely among suitable recipient strains (Yoo et al, 2006;Deplano et al, 2007;Kawalec et al, 2007;Borgmann et al, 2007;Werner et al, 2007c;Hsieh et al, 2009).…”
Section: Prevalence Of Vre Among the Hospital Settingmentioning
confidence: 99%
“…Diagnostic and university laboratories send strains to us for (vancomycin/teicoplanin) resistance confirmation and molecular typing. Our enterococcal strain collection currently contains > 10,000 isolates, mainly from hospital surveillance and infections, but also from animals, food products, the environment, and stool colonisations in outpatients (Klare et al, 1995a, Klare et al, 1995b, Klare et al, 1999, Klare et al, 2005, Werner et al, 2007, Werner et al, 2010and Werner et al, 2011a. Until now, we collected and identified 1060 vanB strains including 982 vanB-positive E. faecium and 74 vanB-positive E. faecalis which were all from hospital patients.…”
Section: Strain Collectionmentioning
confidence: 99%
“…Although some hospitals have reported only sporadic fi ndings, others have been faced with extended outbreaks (2)(3)(4)(5). Apart from threatening patient health, these pathogens have an unfavorable economic impact on resources for healthcare in general.…”
Section: R Ecently Vancomycin-resistant Enterococcus Faeciummentioning
confidence: 99%
“…Apparently, this did not jeopardize the usefulness of the outbreak alert method we used. Second, other hospitals in the region also had reports about clusters of VRE (5). Therefore, hygienic measures may also have been hampered by admission of some colonized patients from outside the hospital (9).…”
Section: R Ecently Vancomycin-resistant Enterococcus Faeciummentioning
confidence: 99%